Is elective neck dissection necessary in cases of laryngeal recurrence after previous radiotherapy for early glottic cancer?. Issue 12 (24th November 2014) - Deganello, A; Meccariello, G; Bini, B; Paiar, F; Santoro, R; Mannelli, G; Gallo, O
Abstract Objectives: To assess the clinical utility of elective neck dissection in node-negative recurrent laryngeal carcinoma after curative radiotherapy for initial early glottic cancer. Methods: A retrospective review was undertaken of 110 consecutive early glottic cancer patients who developed laryngeal recurrence after radiotherapy (34 recurrent T1, 36 recurrent T2, 29 recurrent T3 and 11 recurrent T4a) and received salvage laryngeal surgery between 1995 and 2005. Results: Six patients presented with laryngeal and neck recurrence and underwent salvage laryngectomy with therapeutic neck dissection, 97 patients with recurrent node-negative tumours underwent salvage laryngeal surgery without neck dissection and only 7 underwent elective neck dissection. No occult positive lymph nodes were documented in neck dissection specimens. During follow up, only three patients with neck failure were recorded, all in the group without neck dissection. There was no significant association between the irradiation field (larynx plus neck vs larynx) and the development of regional failure. A higher rate of post-operative pharyngocutaneous fistula development occurred in the neck dissection group than in the group without neck dissection (57.2 per cent vs 13.4 per cent, p = 0.01). Multivariate logistic regression analysis showed that early (recurrent tumour-positive, node-positive) or delayed (recurrent tumour-positive, node-negative) neck relapse was not significantly related to the stage of the initial tumour or the recurrent tumour. An age of less than 60 years was significantly associated with early neck failure (recurrent tumour-positive, node-positive). Conclusion: Owing to the low occult neck disease rate and high post-operative fistula rate, elective neck dissection is not recommended for recurrent node-negative laryngeal tumours after radiation therapy if the initial tumour was an early glottic cancer.